PARTISIPASI ANGGOTA KELOMPOK WANITA TANI DALAM PEMANFAATAN PEKARANGAN DI KECAMATAN BUMIRATU NUBAN, LAMPUNG TENGAH - Maryati, .; Indaryati, Sri (Indonesian Journal of Socio Economics)
The role of women in the village for exploiting yard yet showed clearly visible although the view emancipation of women get show dynamic for that activities in group most improvement.  The objectives of this research was to identify the participation of women farmer Group. Group members in using their yard and the factor correlation of participation planning, actuating, monitoring and evaluation members in using their yard.  This research was held in Bumiratu Nuban District, Mid Lampung from June to August 2007.  The primary data was taken by interview technique from 45 respondents out of 290 populations. Therespondents were randomly selected.Rank Spearman analysis is used in this study.  The technical sampling is simple multistage cluster sampling.  The study shows participations of group members in using their yard have more high and that have correlations of participation members with using their yard in Bumiratu Nuban District, Mid Lampung.